PROBLEM OF CHOICE ERP-SYSTEM - Anna A. Varshavskaya; Alla A. Protasova (Статистика и экономика, 2016)
The article describes the criteria for selecting the ERP-system and groups of risk of such systems. The descriptions of the leaders of the Russian market of ERP-systems, which have shown good results over the years of its existence in Russia, are given. The solution of such problem is a synthesis of the views of their own and third-party experts. A company will be glad with the system, if it is chosen in such way.